Association of Life’s Essential 8 with all-cause mortality in asthma patients: evidence from NHANES 2005–2018 - Zhu, Jinqi; Tao, Ran; Zhao, Sue (Frontiers in Nutrition, 2025)
BackgroundResearch indicates that Life’s Essential 8 (LE8) has health-promoting effects for many diseases, yet few studies have explored its association with asthma patients. This research aimed to investigate the relationships between LE8 and all-cause mortality in asthma patients.MethodsWe conducted a retrospective cohort analysis of seven cycles of data from the 2005–2018 National Health and Nutrition Examination Survey (NHANES). The impact of LE8, which includes four health behaviors (diet, physical activity, smoking, and sleep) and four health factors (BMI, lipids, blood glucose, and blood pressure), on asthma mortality was analyzed using multivariate Cox proportional hazards models. Dose–response relationships between these indicators and mortality were examined using restricted cubic spline (RCS) analysis. Subgroup analyses and interaction tests were performed to verify the stability of the results.ResultsThe study included 3,321 asthma patients aged 20 or older, with a median follow-up of 91.03 months, during which 331 patients died. Each one-unit increase in LE8 score was associated with a 1.4% reduction in all-cause mortality risk (HR = 0.986, 95% CI: 0.974–0.998; p < 0.001). Patients with scores ≥80 had a 58.8% lower mortality risk than those with scores <50 (HR = 0.412, 95% CI: 0.203–0.837, p = 0.014). Each one-point increase in health behavior score was linked to a 1.3% decrease in mortality risk (HR = 0.987, 95% CI: 0.982–0.992; p < 0.001). Participants with optimal health behaviors (scores ≥80) had a 53.8% lower mortality risk than those with poor scores (<50; HR = 0.462, 95% CI: 0.275–0.777; p = 0.004). RCS analysis revealed linear associations of LE8 and health behavior scores with mortality, while the relationship between health factor scores and mortality was non-linear, with mortality risk decreasing as scores increased above 80. Subgroup analyses showed stable associations between exposure variables and mortality, particularly strong protective associations in high-income groups.ConclusionOptimized LE8, health behavior scores, and health factor scores above 80 are associated with reduced all-cause mortality risk in asthma patients, supporting ideal cardiovascular health as an intervention strategy to lower asthma mortality.